A Replicating RNA Molecule Suitable for a Detailed Analysis of Extracellular Evolution and Replication - Kacian, D. L. (1972)
The aim of the present study is to make available a replicating molecule of known sequence. Accordingly, we sought a molecule that has the following properties: (a) replicates in vitro in a manner similar to phage Qβ RNA; (b) produces antiparallel complementary strands that can be separated from one another; and (c) is small enough to yield its sequence with reasonable effort. We report here the isolation of a replicating RNA molecule that contains 218 nucleotides and possesses the other features desired for a definitive analysis of the replicating mechanism. Despite its small size, this molecule can mutate to previously determined phenotypes. It will, therefore, permit the precise identification of the base changes required to mutate from one phenotype to another in the course of extracellular Darwinian selection experiments.